Phytoplankton Community Structure in Carocok Tarusan Beach Pesisir Selatan Regency West Sumatra Province - Adrizal, Taufik; Siregar, Sofyan Husein; Nurrachmi, Irvina (Journal of Coastal and Ocean Sciences, 2022)
The existence of phytoplankton in the aquatic environment greatly affects aquatic life itsself. Through photosynthesis, phytoplankton is responsible for producing oxygen and nutrients, especially for other marine organisms. Furthermore, phytoplankton can be indicators of fertility and the quality of an aquatic ecosystem. The waters of Carocok Tarusan beach have congested anthropogenic activities, like shipyard and shipping, tourism, and domestic activities. This of course greatly affects the existence of phytoplankton which is very dependent on environmental conditions. This study aims to determine the structure of the phytoplankton community and its relation to the characteristics along with the quality of the waters in Carocok Tarusan beach. Phytoplankton samples were collected by using plankton net number 25 at three stations that have been determined by the purposive sampling method. The results showed that the temperature values ranged from 29.3-29.7ºC, salinity 27.7-31.3‰, brightness 1.8-3 m, pH 7, 0.3-0.6 m/s. There are 12 species from 3 classes found. The most common species found were Navicula sp, Synedra ulna sp., and Isthmia sp. The average abundance of phytoplankton at each station is 57.86-92.58 Ind/L. The results of the ANOVA test on the abundance of phytoplankton showed a significant value of 0.108, which means the P value> 0.05, this indicates that there is no significant difference in the abundance of phytoplankton between stations. The value of the species diversity index (H') of phytoplankton has an average value of 1.7436 - 2.0028. The Uniformity Index (E) has an average value ranging from 0.1393 to 0.1464. Meanwhile, the phytoplankton dominance index shows an average value of 0.2661 – 0.3191.